2020
DOI: 10.3390/agronomy10081138
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Modulates the Production and Composition of Phenols in Barley under Aluminum Stress

Abstract: Silicon (Si) exerts beneficial effects in mitigating aluminum (Al) toxicity in different plant species. These include attenuating oxidative damage and improving structural strengthening as a result of the increased production of secondary metabolites such as phenols. The aim of this research was to evaluate the effect of Si on phenol production and composition in two barley cultivars under Al stress. Our conceptual approach included a hydroponic experiment with an Al-tolerant (Sebastian) and an Al-sensitive (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Mineral fertilization may also lead to soil acidification thereby increasing aluminum (Al 3+ ) toxicity [7,24,25]. In this context, Vega et al [26] studied the beneficial effects of silicon application for mitigating Al 3+ toxicity in sensitive barley cultivars. Their findings revealed that silicon fertilization could increase the resistance of barley to Al 3+ toxicity by regulating the metabolism of phenolic compounds with antioxidant and structural functions.…”
Section: Smart Fertilizer Development and Their Effect On Soils And P...mentioning
confidence: 99%
“…Mineral fertilization may also lead to soil acidification thereby increasing aluminum (Al 3+ ) toxicity [7,24,25]. In this context, Vega et al [26] studied the beneficial effects of silicon application for mitigating Al 3+ toxicity in sensitive barley cultivars. Their findings revealed that silicon fertilization could increase the resistance of barley to Al 3+ toxicity by regulating the metabolism of phenolic compounds with antioxidant and structural functions.…”
Section: Smart Fertilizer Development and Their Effect On Soils And P...mentioning
confidence: 99%
“…Figure 5 illustrates the chemical structures of selected phenolic compounds, focusing on the flavonoids and phenolic acids described in the literature [72,109,232].…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Figure 5 illustrates the chemical structures of selected phenolic compounds, focusing on the flavonoids and phenolic acids described in the literature [72,109,232]. Researchers have suggested the presence of several potential links between silicon and phenol metabolism: (i) silicon could interact with the OH groups of phenols by condensing with Si(OH) in biological systems, (ii) silicon may be involved with lignincarbohydrate complexes present in cell walls, and (iii) silicon might play a role in signal transduction pathways responsible for inducing lignin production [193,233,234].…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Si application is important in mitigating Al toxicity by minimizing transpiration and maximizing photosynthesis 28 , 29 , increasing phenolic compounds, especially lignin 10 , 21 , 22 , enhancing enzyme activity 6 , 30 , and macros- and micronutrients uptake 6 , 10 , 12 . Several studies with various species found that, Si supplementation enhances plant responses to the toxic effects of Al in plants such as wheat 31 , maize 32 , rice 33 , and barley 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane was selected in this study due to its hyperaccumulation of Si 8 , 34 , which is suitable for studying the mechanisms of Si-mediated Al tolerance. Currently, most studies on the amelioration of Al toxicity by Si are based on growth and physiological levels 22 , 35 , while the role of Si in root morphoanatomy under Al stress is still limited. Therefore, the objective of this study was to evaluate the interactive role of Si in increasing the growth, physiological and morphoanatomy responses of sugarcane plants under Al toxicity.…”
Section: Introductionmentioning
confidence: 99%